Dynamic mechanical characterization and modelling of polypropylene based organoclay nanocomposite - Kui Wang (137551) (2015)
In order to investigate the dynamic behaviour of polypropylene based organoclay nanocomposite, the polypropylene matrix and a master batch of polypropylene modified anhydrid maleic were mixed by means of melt mixing technique. The experimental characterization was performed by using split Hopkinson pressure bars (SHPB), at different strain rates and temperatures. A significant increase of the yield stress of nanocomposite was shown with the present of organoclay, comparing to neat PP. A three-phase approach based on the micromechanical formulation of the cooperative model is proposed to model the yield behaviour of the polymer nanocomposite. Our proposed approach accounts for strain rate and temperature effects as well as the organoclay exfoliation effect. The predictions of models for the nanocomposite yield behaviour showed a good agreement with experimental data. Other Information Published in: EPJ Web of Conferences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1051/epjconf/20159402025